Forecasting the spatial variation of optimal sea surface temperature for common squid (Todarodes pacificus) in the Korean jigging fishery - Kim, Moo-Jin; Kim, Changsin; Kim, Hyun Woo; Ji, Hwan-Sung; Kang, Heejoong (Frontiers in Marine Science, 2025)
The decline in common squid (Todarodes pacificus) stocks, combined with increasing environmental variability, underscores the need for science-based approaches to support adaptive fisheries management in Korea. This study aimed to standardize the catch per unit effort (CPUE) of common squid in Korean waters, specifically in the offshore jigging fishery, by incorporating spatiotemporal and sea surface temperature (SST) factors, and to assess future shifts in thermally suitable fishing grounds under the shared socioeconomic pathway 3-7.0 (SSP3-7.0) climate change scenario. A generalized additive model (GAM) revealed a significant nonlinear relationship between CPUE and SST, with squid abundance concentrated within the 13–23 °C range. The peak response was observed around 21 °C, which was identified as the species’ optimal temperature. We applied this preferred thermal range to projected SST data for 2050 and 2100 under the SSP3-7.0 scenario to map the spatial extent of thermally suitable habitats. Results indicated a contraction of suitable fishing areas during the main fishing season (September–October), while suitable temperatures reemerged in November, suggesting a potential delay in fishing ground formation. These findings highlight the importance of flexible fishery scheduling and management criteria in response to climate-driven changes in habitat suitability. This study provides foundational insights for spatially explicit resource management and the development of climate-adaptive fishery strategies.